2012
DOI: 10.1590/s0102-05362012000300020
|View full text |Cite
|
Sign up to set email alerts
|

Alelopatia de extratos de diferentes órgãos de mulungu na germinação de alface

Abstract: Allelopathy of extracts of different organs of coral tree on the germination of lettuce

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 11 publications
1
11
0
9
Order By: Relevance
“…According to Ferreira and Borghetti (2004), allelopathic effects are more evident in characteristics related to growth than in the germination process. Oliveira et al (2012a) confirmed this for Caatinga species with E. velutina flower, bark and seeds extracts and for C. ferrea extracts (OLIVEIRA et al, 2012b) and for Z. joazeiro extracts (Oliveira et al (2012c). This study supports the findings of Ferreira and Borghetti (2004) for melon emergence in sand, which were consequences of the germination process.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…According to Ferreira and Borghetti (2004), allelopathic effects are more evident in characteristics related to growth than in the germination process. Oliveira et al (2012a) confirmed this for Caatinga species with E. velutina flower, bark and seeds extracts and for C. ferrea extracts (OLIVEIRA et al, 2012b) and for Z. joazeiro extracts (Oliveira et al (2012c). This study supports the findings of Ferreira and Borghetti (2004) for melon emergence in sand, which were consequences of the germination process.…”
Section: Resultssupporting
confidence: 86%
“…The release of these compounds can occur via root exudation, leaching or volatilization (REIGOSA et al, 2013). The leaf is the most metabolically active plant organ and thus, possesses a high allelochemical diversity (TUR et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes lead to physical and temporal modifications in the germination process through changes in the germinability, sync and mean time of germination and growth through development inhibition (Ferreira and Aquila, 2000;Oliveira et al, 2012). As observed by Pereira et al (2014), these results indicated that the roots are more sensitive to phytotoxic than the hypocotyl.…”
Section: Discussionmentioning
confidence: 87%
“…Brito et al (2016) utilizando o preparado aquoso de folhas de Myracrodruon urundeuva observaram que quando usada a solução de 75%, houve redução do crescimento da altura das plântulas de cebolinha. Oliveira et al (2012) avaliando interferência alelopática de Erythrina velutina Willd quando utilizado o extrato aquoso de distintas partes dessa espécie, além de observarem muitas anormalidades nas plântulas, evidenciaram que os preparados de cascas proporcionaram os menores valores da altura e da raiz, quando comparada à testemunha.…”
unclassified